基于ANSYS的搅拌摩擦点焊机器人的有限元分析 - 张松; 乔凤斌; 张华德; 刘玉来 (Jixie chuandong)
The 3D model of the friction stir spot welding robot is established,and by engineering analysis software ANSYS grid division,the modal analysis and the static analysis are carried out after simplified its key components model.The inherent frequency and vibration mode and the stress,deformation distribution and so on are obtained,the theory basis for further optimization design is provided.